Improving learning outcomes in an Object-oriented Programming Course, using a flipped classroom - Morais, Paula (2020)
Object Oriented Programming has been a core discipline in Computer Science studies. However, students often have difficulties in learning subjects related to programming. The reasons for these difficulties are well described in the literature and are mainly related to the abstract nature of the subject. To improve the learning process, different teachers are using different active learning methodologies, such as flipped classroom, project-based learning, and peer instruction. This paper describes an experiment conducted to improve the learning experiences of the students attending an Object-Oriented Programming course, form the first year of an Informatics B.Sc. curriculum, using a flipped classroom methodology. One of the learning outcomes in this course aims that students understand the concepts and constructs intrinsic to the object-oriented programming paradigm. Two fundamental concepts arise, the concept of class and the concept of an object. From experience, it is notorious the difficulty students have in learning those. The experiment took place during a class, divided into two moments: at moment one, students were expected to explore the topics, which were then discussed and worked on at moment two. As a final objective the students, who were organized in groups, produced a poster, summarizing the two concepts. The posters were posted on the classroom board. As in the gallery walking strategy, students in groups move through the posters and interact and share knowledge. After the class students were asked to answer an anonymous questionnaire aiming to know their opinion on the use of these pedagogical strategies. Two kinds of results were observed: first, the posters and knowledge sharing moment allowed to recognize that students achieve the desired learning outcome. Second, from the questionnaire answers, it was evident that the use of this methodology was well accepted by the students improving their engagement.